Analisis Peramalan Persediaan Batu Bara dengan Pendekatan Time Series (Studi Kasus: Pada PT. X) - Kurniyawan, Aldy; Febryanto, Indra Dwi (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
The manufacturing industry requires a consistent supply of raw materials to maintain a smooth production process, but inventory control is often a major problem faced by companies. This research focuses on forecasting coal needs at PT X using the time series method as well as proposals for safety stock planning, reorder points, and the application of the optimal Economic Order Quantity (EOQ) method. This study aims to determine the comparison of company calculations with EOQ calculations, determine the results of forecasting the amount of coal usage in the next period using time series, and determine the results of calculating the optimal amount of coal orders using the EOQ method. The most optimal EOQ results are 784 tons per order with a more efficient ordering frequency of up to 12 times. The appropriate ARIMA forecasting model is the ARIMA (1,0,1) model with a total coal usage of 6204 tons. From the forecasting of coal usage, the application of the EOQ method is carried out which results in an order quantity of 452 tons of orders at a frequency of 14 times.